ANTI-DIABETIC EFFECTS OF SOME MEDICINAL PLANTS IN EXPERIMENTAL ANIMALS: A REVIEW - Maqbool, Mudasir; Gani, Imran; Dar, Mohmad Amin (Asian Journal of Pharmaceutical Research and Development, 2019)
Diabetes is a chronic endocrine disease with global prevalence and increasing incidence. Diabetes presents with a major health issue in all age groups in the present times owing to its multisystem involvement and serious complications. In spite of drug development and therapeutic interventions, successful treatment of diabetes still remains a challenge and worldwide research is focused on finding alternative modalities. By conducting sizable amount of analytical work, numerous traditional medicines have been found for diabetes. Substances and extracts isolated from completely different natural resources particularly plants have perpetually been a fashionable arsenal for dominant and treating polygenic disorders downside and complication arising because of it. Many medicinal plants have shown promising effects in experimental animals which can be extrapolated to humans also. In this paper, we will review various medicinal plants showing anti-diabetic activity in experimental animals.